Experimental strength of single-lap hybrid joints on woven fabric kenaf fiber composites under quasi static condition - Lee, Sim Yee; Ahmad, Hilton (EDP Sciences, 2016)
For the past decades, usage of natural fiber reinforced composites in low bearing load applications are increasing tremendously due to drawbacks concerning the use of synthetic fibers. Kenaf fibers have a good potential to be used as composite reinforcements as they possesses excellent fiber strength compared to own self-weight. Current work concentrates on mechanical properties of woven fabric kenaf composites with single-lap hybrid joints configurations. Four width to diameter ratio, (W/d) of cross-ply lay-up joints as designed in testing series were tested by using quasi static mechanical testing. Experimental results showed that the failure load increased with the increasing of W/d ratios. Thinner lay-up had better bearing strength compared to thicker lay-up as found in current study.